The Urban South : A History - Larsen, Lawrence H. (Lawrence Harold), 1931-2017 (Book collections on Project MUSE., 1990)
In this panoramic survey of urbanization in the American South from its beginnings in the colonial period through the ""Sunbelt"" era of today, Lawrence Larsen examines both the ways in which southern urbanization has paralleled that of other regions and the distinctive marks of ""southernness"" in the historical process. Larsen is the first historian to show that southern cities developed in ""layers"" spreading ever westward in response to the expanding transportation needs of the Cotton Kingdom. Yet in other respects, southern cities developed in much the same way as cities elsewhere in Amer.